Pembelajaran Daring di Tengah Wabah Covid-19 - Rosyidi; Unsiyah Jamilah (MUKASI: Jurnal Ilmu Komunikasi, 2022)
Communication is very important in the learning process with good communication, the teaching and learning process run well. In the learning process, lecturers communicate with students using various methods, both direct and indirect communication. The COVID-19 pandemic that has hit the world, including Indonesia, has changed the teaching and learning process around the world. The learning and teaching process is on average carried out remotely or online learning. The purpose of this research is to categorize communication patterns in the learning process carried out by lecturers in communicating on campus online, and see the factors that are obstacles and solutions to learning. This study concluded that the communication pattern that is often used is the saxunder communication pattern because it is an effective communication pattern and prevents contracting the Covid-19 virus. The inhibiting factors of the communication process are obstacles from the delivery of the message, the recipient of the message, technical barriers, physical barriers, semantic barriers, and psychological barriers. Meanwhile, the solution is that the lectures gaves a time gap in advance, providing free internet facilities to the learner.